E-Modul Pembelajaran Dasar-dasar Teknik Ketenagalistrikan di Kelas X Teknik Ketenagalistrikan - Selvy Desviana; Hansi Effendi (Jurnal Pendidikan Teknik Elektro, 2023)
This research aims to create a learning e-module themed "Fundamentals of Electricity Engineering" especially on elements 5 and 7, for class X students in the Electricity Engineering department. This e-module is designed to improve the quality of learning, teaching, and the learning process in the subject. The research method used is Research and Development (R&D) by adapting the 4-D development model. As the name 4D implies, this model has four stages of development: define, design, develop, and disseminate. Data needs were obtained through observations, interviews, and questionnaires given to teachers and students of class X Electricity Engineering. This e-module is designed by following the principles of learning design that are interesting, interactive, and following the characteristics of students. The e-module is equipped with images and videos to facilitate understanding complex concepts. After the e-module was developed, a limited trial was conducted with several students in Class X Electricity Engineering to evaluate the feasibility of this e-module. The data obtained from the trial were analyzed, and the results showed that the learning e-module "Fundamentals of Electricity Engineering" received a score of "very valid" from the approver and "very practical" from teachers and students. Thus, the learning e-module "Fundamentals of Electricity Engineering" can be used as a learning tool. Thus, this learning e-module, "Fundamentals of Electricity Engineering" is expected to be an effective alternative for improving the quality of learning in class X Electricity Engineering. Using e-modules is expected to help students understand learning materials and improve learning achievement.